Effects of seminal plasma ionic content, pH and osmolality on spermatozoa motility in bester (Female Huso huso × Male Acipenser ruthenus) sturgeon - Baradaran Noveiri, S.; Noori, A.; Bahmani, M.; Yazdani Sadati, M.; Akbarzadeh, A. (2019)
The ionic contents, pH and osmolality of seminal plasma and their relationships to sperm motility indices (sperm motility duration and percentage of motile sperm) were evaluated in bester. Semen was collected from six bester specimens and their seminal plasma was evaluated. The seminal plasma contained 54.5±2.8 mM sodium, 22.33±2.5 mM chloride, 7.1±1.2 mM potassium, 3.55±0.6 mM calcium and 0.58±0.09 mM magnesium. The result shows that Na+, Cl- and K+ (54.5±2.8, 22.33±2.5 and 7.1±1.2 mM, respectively) were predominant ions in bester seminal plasma like other sturgeons. However the concentrations of K+, Ca2+ and Cl- in bester seminal plasma were higher than those reported in beluga and sterlet as parental species. The mean pH and osmolality of seminal plasma were 8.09±0.34 and 127.6±20.8 mOsm kg-1, respectively. A significant negative regression was observed between osmolality and percentage motility (r=- 0.893). Published